Determinants of Financial Reporting Standards Implementation in Indonesian MSMEs: An Empirical Study of Songket Koto Gadang Enterprises - Rizka Fadhilah; Immu Puteri Sari; Rina Widyanti; Fitri Yulianis (Journal of Emerging Economics and Business, 2026)
The implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) is expected to enhance financial reporting quality and support the long-term sustainability of micro, small, and medium enterprises (MSMEs). However, its adoption among Indonesian MSMEs remains limited due to organizational and managerial challenges. This study investigates the effects of accounting recording systems, accounting understanding, and MSME readiness on the implementation of SAK EMKM among Songket Koto Gadang MSMEs in Agam Regency, West Sumatra. A quantitative explanatory survey was conducted involving 100 MSME owners selected through purposive sampling. Data were collected using structured questionnaires and analyzed through multiple linear regression with IBM SPSS Statistics. The results indicate that accounting recording systems, accounting understanding, and MSME readiness significantly influence the implementation of SAK EMKM, both partially and simultaneously. However, the negative coefficients of accounting recording systems and accounting understanding suggest that accounting knowledge and existing recording practices alone are insufficient to ensure effective implementation. MSME readiness emerged as the strongest determinant of successful adoption. These findings emphasize the importance of organizational preparedness, managerial commitment, and continuous institutional support in promoting SAK EMKM implementation. The study provides empirical evidence that can inform policymakers and supporting institutions in developing targeted accounting training, mentoring, and capacity-building programs to improve financial reporting practices among traditional craft-based MSMEs.